EVALUATION OF MAIN INDEXES OF IMMUNE STATE IN THE PATIENTS WITH PERCUTANEOUS TRANSLUMINAL CORONARY ANGIOPLASTY WITH STENTING - O. S. Shkoda; A. N. Shilova; V. S. Kozyreva; A. M. Chernyavsky (Медицинская иммунология)
The study included thirty-one patients with coronary heart disease before the procedure of percutaneous transluminal coronary angioplasty with stenting and the day after the surgery. Flow cytometric assays were performed in order to determine major subpopulations of peripheral lymphocytes (CD3+CD19- , CD3- CD19+, CD3- CD16+CD56+, CD3+CD16+CD56+). A statistically significant decrease in the relative amount of total T-lymphocytes and increased relative content of NK and NK-T-cells was revealed in the patients under study when compared with healthy donors. The decrease in CD3+CD19- subpopulation did correlate with increased CD3- CD16+CD56+ lymphocyte set. We have not found any significant changes of immune profile at the early terms post-surgery, when compared with appropriate results obtained pre-surgery.